A Review of Qualitative Investigation of Food Safety Based on Good Governance - Mahmudiono, Trias; MAJED, Hasan Shamel; Widjaja , Gunawan; SHICHIYAKH, Rustem Adamovich; KOMARIAH, Aan; YASIN, Ghulam; ISWANTO, Acim Heri; KADHIM, Mustafa Mohammed; AL-REKABY, Heba Qassim; SINGH, Krishanveer (Food Science and Technology, 2023)
Food safety agencies (FSAs) were formed across the globe as part of a series of food risk (FR) governance changes made in reaction to ongoing food crises in an endeavor to control increasingly industrialized, globalized, and hazardous food chains. Given such substantial changes in governance, little research has been done on how consumers react to, reject, and/or participate with the mentioned new governance systems in non-crisis situations. As a result, the current study looks at how FR is managed on a daily basis from the consumers’ perspective, whose voices are often ignored in food policies. Consumer lived experiences, priorities, and views pertaining to FR governance and the food safety (FS) authority, in particular, are investigated using empirical data from focus groups performed with the general public. This study is framed by a normative framework of multi-scalar governance and what makes it successful or good. As a result, the study promotes FR policy discussions via the lens of normative good FR governance, involving a consumer-perceived assessment of the perceived accountability, openness, and efficacy of FR governing mechanisms. The article closes by constructively considering the potential and constraints of adopting more adaptable forms of governance in the multi-scalar and changing the policy framework that defines FR.